2017
DOI: 10.1080/02699931.2017.1320978
|View full text |Cite
|
Sign up to set email alerts
|

Can perceivers recognise emotions from spontaneous expressions?

Abstract: Posed stimuli dominate the study of nonverbal communication of emotion, but concerns have been raised that the use of posed stimuli may inflate recognition accuracy relative to spontaneous expressions. Here, we compare recognition of emotions from spontaneous expressions with that of matched posed stimuli. Participants made forced-choice judgments about the expressed emotion and whether the expression was spontaneous, and rated expressions on intensity (Experiments 1 and 2) and prototypicality (Experiment 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 41 publications
3
52
1
1
Order By: Relevance
“…They were thus not real-life emotional expressions. While the methods of emotion simulation offer high experimental control, the validity of prosodic stimuli derived from these measures is limited (Scherer, 1986 ) and may boost recognition accuracy (Sauter and Fischer, 2017 ). Previous studies found that speakers often portray stereotypes of emotions and might differ in the quality of their emotional portrayals (e.g., one speaker might be very good at portraying happiness but not fear, whereas another speaker's performance might show the opposite pattern; Scherer, 1986 ; Banse and Scherer, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were thus not real-life emotional expressions. While the methods of emotion simulation offer high experimental control, the validity of prosodic stimuli derived from these measures is limited (Scherer, 1986 ) and may boost recognition accuracy (Sauter and Fischer, 2017 ). Previous studies found that speakers often portray stereotypes of emotions and might differ in the quality of their emotional portrayals (e.g., one speaker might be very good at portraying happiness but not fear, whereas another speaker's performance might show the opposite pattern; Scherer, 1986 ; Banse and Scherer, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that acted vocalizations are similar, but not identical, to spontaneous expressions. Thus, in future research, potential differences between acted and spontaneous vocalization, as well as the role of emotional intensity, should be considered (see also Sauter & Fischer, 2018).…”
Section: Methods For Eliciting Emotional Vocalizationsmentioning
confidence: 99%
“…A third limitation is that, as with many standardised tests, the emotional expressions we used to evaluate accurate recognition were posed by actors. Although there is evidence that recognition of posed and spontaneous facial expressions overlaps considerably (Sauter & Fischer, 2018), more research with emotional expressions in real life situations may provide additional insight into the role of emotion differentiation in emotion recognition. This work may also include other kinds of emotional expressions, such as speech content.…”
Section: Limitationsmentioning
confidence: 99%